Art of Governmentality in Construction of Russian Woman’s National Identity - Leila Khadem Makhsuos Hosseini (Сравнительная политика, 2024)
Russia's heteronormative policies have been receiving substantial attention mainly from Western scholars, who condemn the gendered-based regularization of identities in Russian cultural politics. I investigate the potential of these policies in legitimizing domestic power, creating a counter-hegemony, and the potential of geopolitical influence confronting Western global hegemony. The paper addresses the discursive construction of auto-governing subjects to illuminate the way national identity is fashioned by the art of governmentality. Methodologically it is mapped on the Foucauldian reading of Gramsci, assuming that the art of governmentality can be a way to win the consent of subjects to ensure hegemony. To examine governmentality, I demonstrate how the liberty of women is controlled in a rational as well as an affective milieu. The article demonstrates that Russian dominant discourses, such as commercials, depict viable female identity in line with traditional gender norms. However, social promotion, and idealization of the female body, are new aspects of a Russian woman in contrast to the USSR discourse of sexual silencing. Women in a rational milieu calculate and decide to choose the viable, rather than marginalized non-heteronormative female identity. In the affective milieu, women's identity construction is controlled by the affections produced by various discourses, such as media. Self-governing subjects consent to traditional female identity, which gives them subjectivity while legitimizing the state power. Depiction of corrupted western moralities in opposition to Russian ethics elicits a sense of threat versus promise, alien versus us. These affections secure against non-heteronormative female identity. It is concluded that delineating the borders between morally deviant West and ethical Russia has the potential of creating a geopolitical hegemony of Russia as the global savior.